Interpretation Of Phraseological Units with the Zoonyms "Cow" and "Bull" in the English and Uzbek Languages (Texas Journal of Multidisciplinary Studies, 2023)
This article is devoted to comparison of phraseological units with component zoonym “cow” and “bull” in two genetically different languages: Uzbek and English. Names of animals in the structure of phraseological expressions are connected with anthropocentric aspect. They demonstrate character, temperament, behaviour, appearance of person